The Role of Strategic Entrepreneurship in Promoting Strategic Innovation: Exploratory Research in Private Universities and Colleges in the Middle Euphrates Region - Dr. Emad Wahab Al-Husseini; Lecturer Suhad Hussain Shyae; Assistant Lecturer Rana Zahir Salman Aljanabi (Peerian Journals Publishing, 2023)
The research aims to identify the role of strategic entrepreneurship in promoting strategic innovation among a sample of private universities and colleges in the Middle Euphrates region. In order for this to happen,The dimensions of strategic entrepreneurship have been adopted (continuous innovation, entrepreneurial mentality, proactive behaviour, risk taking, value creation), and the dimensions of strategic innovation were adopted .(Organizational readiness, managing the innovation process, disciplined implementation, strategic paving), and private universities and colleges (Wareth, Al-Safwa, Al-Zahraa, Al-Taf, Al-Mustaqbal, Al-Hillah AlDini) operating in the Middle Euphrates region were chosen as an exploratory and analytical field for research. By distributing a questionnaire that included (100) respondents from the deans and heads of departments and divisions and their units to private universities and colleges, the research sample, and the statistical program Smart PLS was used,One of the most important conclusions reached by the research is that the dimensions of strategic entrepreneurship have an effective impact on promoting strategic innovation among the universities and colleges of the research sample in light of the great competition in the educational sector in Iraq .The research concluded with a number of recommendations, the most prominent of which was the need to employ the dimensions of strategic entrepreneurship in strengthening the positive impact relationship between it and the dimensions of strategic innovation within the educational sector, in line with continuing to create services of strategic value for educational institutions and their educational and functional staff. By keeping abreast of developments and seizing opportunities to ensure continuity, growth and survival in the labour market .
Keywords: Strategic Entrepreneurship; Strategic Innovation